The Role of Hops in Flavour Stability – Some Aspects - Schönberger, Christina (BrewingScience, 2012)
What is the role of hops in beer flavour stability? A lot of hop constituents show beneficial properties in terms of supporting the flavour stability of beer. (E.g. alpha acids as well as various polyphenolic compounds have high antioxidant activities). The role of Iso-alpha acids in this context is discussed controversially but also other bitter acids may contribute positively to the flavour stability of beer. In addition to these non-volatile hop compounds hop oil compounds can also play an important role in regard to flavour stability. Therefore different hop products will have different impacts on flavour stability in beer. This paper gives a short overview of today?s knowledge of the role of hops in flavour stability in beer.